INTEGRASI HUMAN RESOURCES SCORECARD DAN HUMAN RESOURCES ACCOUNTING PADA KINERJA PERGURUAN TINGGI (Studi Pengembangan Konsep Pada Universitas Pendidikan Indonesia) - Jaenudin, - (2014)
Persoalan yang dikaji dalam tesis ini adalah pengelolaan sumber daya manusia strategik yang sesuai dengan visi dan misi lembaga pendidikan. Keberadaannya dapat diukur dalam satuan moneter, diakui sebagai asset sumberdaya manusia yang dilaporkan khusus pada laporan keuangan. Tujuan penelitian ini adalah untuk merumuskan rancangan strategis model balanced scorecard, rancangan strategis model human resource scorecard, merancang pengukuran human resources accounting, merancang model integrasi pengukuran kinerja human resources accounting dengan human resources scorecard di UPI serta mengukur perbedaan efektivitas model integrasi pengukuran kinerja human resources accounting dengan human resources scorecard dibandingkan dengan model human resources accounting saja pada aspek pengakuan aktiva, pengukuran SDM, relevansi dan reliabilitas pengukuran SDM UPI. Teori yang digunakan adalah konsep kinerja, balance scorecard, konsep balance scorecard di perguruan tinggi, human resources scorecard, dan human resource accounting dengan pendekatan riset and develompment. Hasil penelitian ini adalah rumusan model balanced scorecard,rumusan model human resource scorecard, rancangan pengukuran human resources accounting dan rancangan model integrasi human resources accounting (HRA) dengan human resources scorecard (HRSC) di UPI. Selain itu, hasil penelitian ini adalah hasil uji beda untuk mengetahui tingkat perbedaan efektivitas model integrasi dibandingkan dengan model HRA saja. Dengan diintegrasikan dan disandarkannya cost dan value SDM human resource accounting pada strategi pengelolaan SDM human resource scorecard, maka pengakuan SDM sebagai aktiva, subjektifitas pengukuran dan revelansi pengukuran SDM telah tersolusikan. Sementara relevansi pengukuran SDM masih belum signifikan, terutama terkait dengan umur ekonomis strategi SDM yang lebih dari jangka waktu yang telah ditetapkan pada sasaran di initiative strategi map integrasi HRA dengan HRSC. Dengan demikian, hal ini direkomendasikan diadakan penelitian lanjutan.   The issues examined in this thesis is the strategic management of human resources in accordance with the vision and mission of the institution . Its presence can be measured in monetary terms , are recognized as assets of human resources specifically reported on the financial statements . The purpose of this study is to formulate a model of balanced scorecard strategic design , strategic design model of human resource scorecard , designing measurement of human resources accounting , performance measurement design a integration model of human resources to human resources accounting UPI scorecard and measure differences in the effectiveness of the integration model of accounting performance measurement of human resources with human resources scorecard compared to models accounting course on human resources aspects of asset recognition , measuring HR , relevance and reliability of measurement of HR UPI . The theory used is the concept of performance , balanced scorecard , balanced scorecard concept in college , human resources scorecard and human resource accounting approach to research and develompment . The results of this study is the formulation of a model of balanced scorecard , scorecard formulation of human resource models , the design of accounting and measurement of human resources integration model design human resources accounting ( HRA ) with human resources scorecard ( HRSC ) on UPI . In addition , the results of this study are the result of different test to determine the level of effectiveness of the integration model differences compared with HRA models only. With integrated and disandarkannya cost and value of human resources in human resource accounting human resource management strategy HR scorecard , the recognition of human resources as assets , the subjectivity of measurement and measurement revelansi HR has tersolusikan . While the relevance of HR measurement is still significant , especially related to the economic life of the HR strategy over a predetermined period of time at the target in the strategy map integration initiative with HRSC HRA . Thus , it is recommended further research conducted .